FASILITAS, TARIF, PROMOSI DAN CITRA MEREK TERHADAP KEPUASAN PENGGUNA TRANSPORTASI ONLINE l(GO-JEK) DI KOTA SURAKARTA - Eva Tusti Anggraini; Djumali Djumali; Sri Hartono (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study is to analyze whether or not the influence of Facilities, Rates, Promotions and Brand Image on Online Transportation (Go-Jek) User Satisfaction in Surakarta City. The population in this study are all online motorcycle transportation users in Surakarta, whose numbers are infinite or unknown. The sampling technique is an infinite number using the Lemeshow formula, with a total of 100 respondents. Data collection uses a Likert scale questionnaire to measure respondents' answers identifying the relationship between Facilities, Rates, Promotions and Brand Image to Online Transportation (Go-Jek) User Satisfaction in Surakarta City. The results show that Facilities, Rates, Promotions and Brand Image influence simultaneously and significantly on Online Transportation User Satisfaction (Go-Jek) in Surakarta City. Facilities a positive and significant leffect on Online Transportation User Satisfaction (Go-Jek) in the City of Surakarta. Rates have a positive and significant effect on Online Transportation User Satisfaction (Go-Jek) in Surakarta City. Promotion has a positive and significant effect on Online Transportation User Satisfaction (Go-Jek) in Surakarta City. Brand Image has positive and significant effect on Online Transportation User Satisfaction (Go-Jek) in Surakarta City. Keywords: Facilities, Rates, Promotion, Brand Image, User Satisfaction